Developing a Conceptual Framework on Retailers’ Performance Towards Tourists’ Shopping Satisfaction - Patwary , Ataul Karim (South Asian Journal of Social Sciences and Humanities, 2020)
Malaysia is well known for its shopping reputation among the tourists, specially from Asian and Middle East countries. Shopping is one of the reasons why international tourists chose to visit Malaysia. During shopping, most of the time international tourists interact with retailers which is the context of this study. This study aims to explore on tourists’ shopping related issues in Malaysia in relation with retailers’ performance and develop a framework which will direct the future researchers to conduct empirical investigations. For the current study, the researcher relied on existing literature in the area of international tourists’ shopping behavior and how it influences on their satisfaction.